EPCT-22 SAFETY AND EFFICACY OF INTRAVENTRICULAR IMMUNOVIROTHERAPY WITH ONCOLYTIC HSV-1 G207 FOR TREATMENT OF LEPTOMENINGEAL DISEASE. (1st June 2021) - Kang, Kyung-Don; Bernstock, Joshua; Mott, Bryan; Nan, Li; Li, Rong; Totsch, Stacie; Gary, Sam; Ghajar-Rahimi, Gelare; Etminan, Tina; Eisemann, Tanja; Wechsler-Reya, Robert; Beierle, Elizabeth; et al.
Abstract: Leptomeningeal metastatic disease (LMD) occurs in 30–50% of newly diagnosed and recurrent pediatric malignant cerebellar tumors and 20–45% of malignant supratentorial tumors. Radiation and chemotherapy often cause substantial long-term neurotoxicity and outcomes remain poor for patients with LMD. At recurrence, LMD is generally minimally responsive to conventional therapies. Immunovirotherapy with engineered oncolytic HSV-1 G207 has emerged as a promising treatment for children with high-grade brain tumors. G207 infects and kills tumor cells while sparing normal cells and stimulates a robust anti-tumor immune response. Intratumoral G207 inoculation demonstrated safety and preliminary efficacy in a pediatric Phase 1 trial in recurrent/progressive high-grade glioma (NCT02457845), and a Phase 2 trial (NCT04482933) is forthcoming. Additionally, a Phase 1 trial of intratumoral G207 in recurrent/progressive malignant pediatric cerebellar tumors is ongoing (NCT03911388). While intratumoral inoculation delivers G207 directly to a primary tumor, it requires neurosurgical procedures thereby limiting repeat doses. Thus, we sought to establish the safety and efficacy of intraventricular G207. Utilizing an immunocompetent, HSV-sensitive murine strain, we determined that a standard 1x10 7 plaque-forming units (PFU) dose of G207 resulted in damage to the ependymal lining. However, interferon induction with an intraventricular low-dose (1x10 4 PFU) of G207 or polyinosinic-polycytidylic acid (poly I:C), a toll-like receptor 3 agonist, three days prior to standard treatment dose protected the ependymal lining. This approach enabled safe delivery of multiple subsequent doses. Importantly, with these protective measures, G207 significantly prolonged survival in pediatric patient-derived xenograft models and an immunocompetent murine LMD model of group 3 medulloblastoma, the most aggressive and fatal subtype. Collectively, these data indicate that toxicity from intraventricular G207 can be safely mitigated prior to a therapeutic dose, and that intraventricular G207 effectively targets group 3 medulloblastoma including LMD. These findings provide support for clinical translation of intraventricular G207.